ЗАМОНАВИЙ НЕМИС ТИЛИ ОҒЗАКИ ВА ЁЗМА НУТҚИДА ИНГЛИЗЧА СЎЗЛАР - Далжанова, С.С.; Тиллахўжаева, Ф.М. (SCIENCE and SOCIETY, 2020)
The article discusses the use of English words in German and the problems that arise in connection with this issue. For this purpose, articles devoted to this problem from Internet sources in Russian, German, and also English were studied and analyzed. Concrete examples of the use of English words in modern magazines were presented. Particular attention is paid to the concept of "Denglisch".